Intolerable cruelty [videorecording (DVD)] - Coen, Ethan; Ramsey, Robert, 1962-; Stone, Matthew, 1963-; Coen, Joel; Clooney, George; Zeta-Jones, Catherine, 1969-; Rush, Geoffrey, 1951-; Cedric, the Entertainer, 1965-; Herrmann, Edward, 1943-2014; Adelstein, Paul; Jenkins, Richard, 1947-; Thornton, Billy Bob; et al. (Universal Pictures, 2004)
Miles Massey is a high-powered Los Angeles divorce lawyer nearing a midlife crisis. While representing his wealthy client Rex Rexroth, Miles meets his match in Rex's gold-digging wife, Marilyn. He's impressed by her similarly heartless ways of using marriage to fuel an expensive lifestyle, but Miles still manages to defeat her in court. With Marilyn looking to get her revenge and Miles finding himself attracted to her, the two engage in a ruthless romantic pursuit to out-swindle each other.